Peripheral blood lymphocyte-to-monocyte ratio as a screening marker for influenza infection. (January 2021) - Patel, Bijal; Oye, Monique; Norez, Daniel; Isache, Carmen
Influenza outbreaks occur annually and account for significant morbidity and mortality. The overall burden of influenza infections, in the USA, for the 2017–2018 season, was an estimated 45 million cases, 810 000 hospitalizations and 61 000 deaths. Literature suggests that leukocyte count and differential, particularly lymphopenia and/or monocytosis, can provide diagnostic value for influenza infection. However, studies regarding these findings are limited in the adult population, particularly in the USA. The objective of this study was to determine if lymphocyte-to-monocyte ratio (L:M)<2 can be used as a screening marker for influenza infection. We performed a retrospective analysis of all patients who presented to University of Florida Health, Jacksonville, a university-affiliated tertiary care center in Jacksonville, Florida, between January 2017 and December 2018, with 'influenza-like' symptoms and who were subsequently admitted to the hospital. Patients were divided into two cohorts, based on whether they had laboratory-confirmed influenza versus another confirmed upper respiratory tract viral infection (influenza-like illness (ILI)). L:M was compared between the two groups and was found to be lower in the influenza group compared with the ILI group (p<0.0001). Results of this study demonstrate that a L:M<2 has significant diagnostic value in the acute phase of influenza and can be used for earlier detection and management of this disease, in order to improve clinical outcomes.